Multi-Gene Analysis Reveals a Lack of Genetic Divergence between Calanus agulhensis and C. sinicus (Copepoda; Calanoida) - Kozol, Robert (Public Library of Science, 2012)
The discrimination and taxonomic identification of marine species continues to pose a challenge despite the growing number of diagnostic metrics and approaches. This study examined the genetic relationship between two sibling species of the genus Calanus (Crustacea; Copepoda; Calanidae), C. agulhensis and C. sinicus, using a multi-gene analysis. DNA sequences were determined for portions of the mitochondrial cytochrome c oxidase I (mtCOI); nuclear citrate synthase (CS), and large subunit (28S) rRNA genes for specimens collected from the Sea of Japan and North East (NE) Pacific Ocean for C. sinicus and from the Benguela Current and Agulhas Bank, off South Africa, for C. agulhensis. For mtCOI, C. sinicus and C. agulhensis showed similar levels of haplotype diversity (H(d) = 0.695 and 0.660, respectively) and nucleotide diversity (π = 0.003 and 0.002, respectively). Pairwise F(ST) distances for mtCOI were significant only between C. agulhensis collected from the Agulhas and two C. sinicus populations: the Sea of Japan (F(ST) = 0.152, p<0.01) and NE Pacific (F(ST) = 0.228, p<0.005). Between the species, F(ST) distances were low for both mtCOI (F(ST) = 0.083, p = 0.003) and CS (F(ST) = 0.050, p = 0.021). Large subunit (28S) rRNA showed no variation between the species. Our results provide evidence of the lack of genetic distinction of C. sinicus and C. agulhensis, raise questions of whether C. agulhensis warrants status as a distinct species, and indicate the clear need for more intensive and extensive ecological and genetic analysis.